STUDY ON THE ACTUAL SITUATION OF DOMESTIC WATER IN 24 MILITARY UNITS IN THE NORTHERN REGION IN 2022 - Tran Quoc Luat; Cao Thi Minh Ngoc; Pham Van Son (Tạp chí Y học Quân sự, 2024)
Purpose: Study on the actual situation of domestic water in some military units in the Northern region in 2022. Subjects and Methods: A cross-sectional descriptive study with analysis and evaluation of seven basic physical, chemical and microbiological indicators on 113 samples of domestic water collected at 24 military units stationed in the Northern Region from July to October, 2022. Results: The water used for consumption and daily activities in the studied units accounted for 58.4% from drilled wells and dug wells and 35.4% from water supplied by factories, in which 61.1% of the water was untreated before use. The proportion of water sources that did not meet the standards according to QCVN 01:2018/BYT for pH indicator was 29/113 samples (25.7%), and for turbidity was 10/113 samples (8.8%). A comparison of nitrite and ammonia standards between treated and untreated water sources showed approximate equality. The difference in permanganate criteria between treated and untreated water sources and the proportion of samples meeting standards according to QCVN 01-1: 2018/BYT was statistically significant with p < 0.05.